Model analysis for a continuum aircraft fuel tank inspection robot based on the Rzeppa universal joint. (May 2018) - Niu, Guochen; Wang, Jinkun; Xu, Kailu
A continuum robot was designed to assist aircraft crew in inspecting fuel tanks, thereby decreasing the workload of fuel tank inspection and improving the efficiency of maintenance. The Rzeppa universal joint and cylindrical helical spring were taken as the joint section of the main body, and the load capacity of continuum robot had been improved greatly. Based on the isokinetic feature of the Rzeppa universal joint, the single-section kinematic analysis of the continuum robot was conducted according to the unit load method of cylindrical helical spring. Next, the influence of variable curvature bending properties of the plant was reduced, and the mapping relationship among the end position, joint variables, and the length of driving cables was obtained. Finally, the simulation and prototype experiments were performed, and the results proved the strong loading capacity of the continuum robot and the effectiveness of the kinematic model.